Beliefs and actions in the trust game: Creating instrumental variables to estimate the causal effect - Miguel A. Costa-Gomes; Steffen Huck; Georg Weizsäcker (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
In many economic contexts, an elusive variable of interest is the agent's expectation about relevant events, e.g. about other agents' behavior. Recent experimental studies as well as surveys have asked participants to state their beliefs explicitly, but little is known about the causal relation between beliefs and other behavioral variables. This paper discusses the possibility of creating exogenous instrumental variables for belief statements, by shifting the probabilities of the relevant events. We conduct trust game experiments where the amount sent back by the second player (trustee) is exogenously varied by a random process, in a way that informs only the first player (trustor) about the realized variation. The procedure allows detecting causal links from beliefs to actions under plausible assumptions. The IV estimates indicate a significant causal effect, comparable to the connection between beliefs and actions that is suggested by OLS analyses.
Keywords: C72; C81; C91; D84; 330; Social capital; trust game; instrumental variables; belief elicitation; Erwartungstheorie; Informationsverhalten; Social Capital; Vertrauen; Spieltheorie; Test; Instrumentalvariablen-Schätzmethode; Kausalanalyse